(untitled) (Iraqi Journal of Medical Sciences, 2019)
Background: Neurotrophic keratopathy as a consequence of laser retinal photocoagulation is not uncommon problem but unfortunately and unfortunately it is not well evaluated in Iraq as well as the world. Objective: To estimate the incidence of neurotrophic keratophathy in association with diode endolaser retinal photocoagulation. Methods: This cross-sectional descriptive study was conducted in vitreoretinal clinic at Ibn-Alhaithum Teaching Eye Hospital in Baghdad. Patients were selected during a period from April 2013 to January 2014, all patients were examined by slit- lamp microscope, and condensing lens + 78 Diopter for dilated fundus examination and cotton wisp to assess corneal sensation. Positive cases documented by anterior segment photograph. Results: The study sample consisted of 108 vitrectomizd eyes of 108 patients, their ages ranged between 5-65 years old with mean of (35.5 years), 42 of them were females and 66 of them were males. By follow up of those patients; 13 of their eyes (12%) developed neurotrophic keratopathy. It had been found that 61.5% of those eyes manifested as stage II, while 30.8% presented as stage I and only 7.7% presented as stage III. Conclusion: Diode endolaser retinal photocoagulation may be an unrecognized reason for neurotrophic keratopathy Keywords: neurotrophic keratophathy, diode endolaser retinal photocoagulation, pars plana vitrectomy, diode laser 810 nm Citation: Al-Quraishi NKM, Mohammad AA, Mahdi HA. Incidence of neurotrophic keratopathy in association with diode endolaser retinal photocoagulation. Iraqi JMS. 2019; 17(1): 18-23. doi: 10.22578/IJMS.17.1.4